2021
DOI: 10.1007/s00415-021-10603-9
|View full text |Cite
|
Sign up to set email alerts
|

MuSK-antibodies are associated with worse outcome in myasthenic crisis requiring mechanical ventilation

Abstract: Myasthenic crisis (MC) is a life-threatening condition for patients with myasthenia gravis (MG). Muscle-specific kinase-antibodies (MuSK-ABs) are detected in ~ 6% of MG, but data on outcome of MuSK-MCs are still lacking. We made a subgroup analysis of patients who presented with MC with either acetylcholine-receptor-antibody positive MG (AchR-MG) or MuSK-MG between 2006 and 2015 in a retrospective German multicenter study. We identified 19 MuSK-AB associated MCs in 15 patients and 161 MCs in 144 patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
0
16
2
Order By: Relevance
“…Here, we investigated clinical features of seronegative MC compared to AChR-MC requiring mechanical ventilation based on our multicenter cohort of MC [ 2 ]. In contrast to MuSK-MCs, which are as old as AChR-MCs [ 5 ], we found that in seronegative MC, patients were younger but that the time between diagnosis of MG and onset of MC was longer compared to AChR-MC. Interestingly, 8 of 17 seronegative MCs had thymic abnormalities.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Here, we investigated clinical features of seronegative MC compared to AChR-MC requiring mechanical ventilation based on our multicenter cohort of MC [ 2 ]. In contrast to MuSK-MCs, which are as old as AChR-MCs [ 5 ], we found that in seronegative MC, patients were younger but that the time between diagnosis of MG and onset of MC was longer compared to AChR-MC. Interestingly, 8 of 17 seronegative MCs had thymic abnormalities.…”
Section: Discussioncontrasting
confidence: 78%
“…Although seronegative MCs were less frequently treated with IVIg, there was no difference in other MC treatments. Furthermore, we did not find any difference in baseline characteristics, in the rate of complications or outcome between the patient groups, which is in contrast to more severely affected MuSK MC patients [ 5 ].…”
Section: Discussionmentioning
confidence: 98%
“…Corroborating previous studies [ 25 , 26 ], we also identified anti-MuSK-ab positivity as an independent risk factor for disease deterioration. Anti-MuSK-ab positive has also been associated with poor outcome of MC [ 27 ]. Interestingly, disease severity as assessed by clinical scoring was a robust predictor for patients at risk for MC or exacerbation, underlining the importance of standardized clinical evaluation of MG patients.…”
Section: Discussionmentioning
confidence: 99%
“…MuSK antibody-positive MG was thought to have more severe symptoms, higher frequency of bulbar muscle and axial muscle involvement, and higher risk of developing myasthenic crisis. 21 , 22 Unlike anti-AChR antibody, MuSK antibodies are mostly IgG4. This subtype of IgG is functionally monovalent, with poor complement activation and low FcγR binding.…”
Section: Discussionmentioning
confidence: 99%